GABA induces the differentiation of small into large cholangiocytes by activation of Ca2+/CaMK I‐dependent adenylyl cyclase 8123. Issue 1 (14th May 2013) - Mancinelli, Romina; Franchitto, Antonio; Glaser, Shannon; Meng, Fanyin; Onori, Paolo; DeMorrow, Sharon; Francis, Heather; Venter, Julie; Carpino, Guido; Baker, Kimberley; Han, Yuyan; Ueno, Yoshiyuki; et al.
Abstract Large, but not small, cholangiocytes (1) secrete bicarbonate by interaction with secretin receptors (SRs) through activation of cystic fibrosis transmembrane regulator (CFTR), Cl−/HCO3− (apex) anion exchanger 2 (Cl−/HCO3− AE2), and adenylyl cyclase (AC)8 (proteins regulating large biliary functions) and (2) proliferate in response to bile duct ligation (BDL) by activation of cyclic adenosine monophosphate (cAMP) signaling. Small, mitotically dormant cholangiocytes are activated during damage of large cholangiocytes by activation of D‐myo‐inositol 1, 4, 5‐trisphosphate/Ca2+/calmodulin‐dependent protein kinase (CaMK) I. gamma‐Aminobutyric acid (GABA) affects cell functions by modulation of Ca2+‐dependent signaling and AC. We hypothesized that GABA induces the differentiation of small into large cholangiocytes by the activation of Ca2+/CaMK I‐dependent AC8. In vivo, BDL mice were treated with GABA in the absence or presence of 1, 2‐bis‐(o‐aminophenoxy)‐ethane‐N, N, N′, N′‐tetraacetic acid, tetraacetoxymethyl ester (BAPTA/AM) or N‐(6‐aminohexyl)‐5‐chloro‐1‐naphtalenesulfonamide (W7) before evaluating apoptosis and intrahepatic bile ductal mass (IBDM) of small and large cholangiocytes. In vitro, control‐ or CaMK I‐silenced small cholangiocytes were treated with GABA for 3 days before evaluating apoptosis, proliferation, ultrastructural features, and the expression of CFTR, Cl−/HCO3− AE2, AC8, and secretin‐stimulated cAMP levels. In vivo administration of GABA induces the apoptosis of large, but not small, cholangiocytes and decreases large IBDM, but increased de novo small IBDM. GABA stimulation of small IBDM was blocked by BAPTA/AM and W7. Subsequent to GABA in vitro treatment, small cholangiocytes de novo proliferate and acquire ultrastructural and functional phenotypes of large cholangiocytes and respond to secretin. GABA‐induced changes were prevented by BAPTA/AM, W7, and stable knockdown of the CaMK I gene. Conclusion: GABA damages large, but not small, cholangiocytes that differentiate into large cholangiocytes. The differentiation of small into large cholangiocytes may be important in the replenishment of the biliary epithelium during damage of large, senescent cholangiocytes. (HEPATOLOGY 2013;)